Hubungan Antara Culture Shock Dengan Hasil Belajar Mahasiswa Tahun Pertama - Zuni Mitasari; Yuswa Istikomayanti (Program Studi bimbingan Konseling PPs UNM Makassar, 2018)
Adjustment to the new environment occurs both internally and externally, so students who can make adjustments gradually will be able to avoid the impact of psychological culture shock. The purpose of this research is to analyze the relationship of culture shock and adjustment to the first year student learning outcomes at Tribhuwana Tunggadewi University. This type of research is quantitative descriptive research with correlational study to determine whether there is a relationship between culture shock and student learning outcomes. Instrument of research data used is questionnaire to test culture shock with four likert scale answer option. Statistical test data obtained r = -0,217 and probability value (Sig. 2-tailed) = 0,054. The conclusion, negative correlation with probability value >0,05 then there is no relation between culture shock with student learning outcomes.